2021
DOI: 10.3390/pathogens10101225
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Nasal Microbiota of Pigs Following Single or Co-Infection with Porcine Reproductive and Respiratory Syndrome and Swine Influenza A Viruses

Abstract: Host-microbiota interactions are important in shaping immune responses that have the potential to influence the outcome of pathogen infection. However, most studies have focused on the gut microbiota and its possible association with disease outcome, while the role of the nasal microbiota and respiratory pathogen infection has been less well studied. Here we examined changes in the composition of the nasal microbiota of pigs following experimental infection with porcine reproductive and respiratory syndrome vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Finally, the presence of an "uncultured" Neisseriaceae member that was most abundant in our community-dwelling SARS-CoV-2-infected group is interesting. This family has been previously reported as a "core" nasopharyngeal microbiome taxon [28] and has been shown to be associated with swine influenza co-infection [29]. However, it's role in SARS-CoV-2 infection remains unclear.…”
Section: Plos Onementioning
confidence: 99%
“…Finally, the presence of an "uncultured" Neisseriaceae member that was most abundant in our community-dwelling SARS-CoV-2-infected group is interesting. This family has been previously reported as a "core" nasopharyngeal microbiome taxon [28] and has been shown to be associated with swine influenza co-infection [29]. However, it's role in SARS-CoV-2 infection remains unclear.…”
Section: Plos Onementioning
confidence: 99%
“…There are many unanswered questions about the impact of changes in the upper respiratory microbiota on PRDC infections. Initial investigations into the impact of IAV on the nasal microbiota of pigs examined animals only during the acute phase of infection or utilized small group sizes, which can reduce confidence in the analysis [ 10 , 11 ]. Additionally, previous research has shown co-infections between IAV and important swine respiratory pathobionts or pathogens alter the host response to infection and worsen the severity of disease [ 18 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have investigated the effect of IAV infection on the swine nasal microbiota. One evaluated the acute phase of IAV infection (through day 5 post-challenge), while the other investigated through the resolution of IAV infection to day 31 post-challenge [ 10 , 11 ]. Both studies found reduced microbial richness post-challenge with IAV, but no change in the time-dependent development of the microbiota [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the presence of an "uncultured" Neisseriaceae member that was most abundant in our community-dwelling SARS-CoV-2-infected group is interesting. This family has been previously reported as a "core" nasopharyngeal microbiome taxon [26] and has been shown to be associated with swine influenza co-infection [27]. However, it's role in SARS-CoV-2 infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%